Benefits of high-dose intravenous immunoglobulin on mortality in patients with severe COVID-19: An updated systematic review and meta-analysis - Xiaosheng Liu; Xiaosheng Liu; Xiaosheng Liu; Yuelun Zhang; Lianfeng Lu; Xiaodi Li; Yuanni Wu; Yang Yang; Taisheng Li; Taisheng Li; Taisheng Li; Wei Cao; et al. (Frontiers in Immunology, 2023)
BackgroundThe clinical benefits of high-dose intravenous immunoglobulin (IVIg) in treating COVID-19 remained controversial.MethodsWe systematically searched databases up to February 17, 2022, for studies examining the efficacy of IVIg compared to routine care. Meta-analyses were conducted using the random-effects model. Subgroup analysis, meta-regression, and trial series analysis w ere performed to explore heterogeneity and statistical significance.ResultsA total of 4,711 hospitalized COVID-19 patients (1,925 IVIg treated and 2786 control) were collected from 17 studies, including five randomized controlled trials (RCTs) and 12 cohort studies. The application of IVIg was not associated with all-cause mortality (RR= 0.89 [0.63, 1.26], P= 0.53; I2 = 75%), the length of hospital stays (MD= 0.29 [-3.40, 6.44] days, P= 0.88; I2 = 96%), the needs for mechanical ventilation (RR= 0.93 ([0.73, 1.19], P= 0.31; I2 = 56%), or the incidence of adverse events (RR= 1.15 [0.99, 1.33], P= 0.06; I2 = 20%). Subgroup analyses showed that overall mortality among patients with severe COVID-19 was reduced in the high-dose IVIg subgroup (RR= 0.33 [0.13, 0.86], P= 0.02, I2 = 68%; very low certainty).ConclusionsResults of this study suggest that severe hospitalized COVID-19 patients treated with high-dose IVIg would have a lower risk of death than patients with routine care.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021231040, identifier CRD42021231040.